THE DISCIPLINE IN THE MAKING: APPRAISING THE PROGRESS OF ISLAMIC ECONOMICS - Furqani, Hafas (Bank Indonesia, 2015)
Islamic economics is currently moving from a mere discourse on economics in Islamic perspective towards becoming a distinct science of Islamic economics. There is a systematic effort from Islamic economic scientific community to develop a discipline of Islamic economics marked by a complete body of knowledge, clear subject matter, methodology/methodologies to appraise theories and continuous growth and accumulation of knowledge. This could be done if the scientific community put strong effort in explicating all the necessary foundations of science and achieve consensus on certain important aspect of discipline. In this paper we attempt to historically survey the development of Islamic economics towards becoming a distinct discipline, evaluate the current practices a adopted by the Islamic economics’ scientific community in settling up problems, and outlining forward agenda in order to achieve this discipline status.